A network management station - Cheah, Kean Hock. (2009)
Internetworking allows several different kinds of devices to participate in the network. The components (the hosts, routers, and media devices) usually are multi-vendor and heterogeneous in nature. A network management technology specific to a particular vendor is unusable in today's environment. An "open" network management technology must be used to manage the network.